Model Pembelajaran Agama Islam bagi Anak Tunagrahita di SDLBYPPLB Padang Sumatra Barat - Aziza Meria (TSAQAFAH, 2015)
Intelectual disable children are categorized as under normal children and slower than others, both in social aspect or inteligency as it is called as mental disorder or intelectual disable. They are stil given by brain but they have intelectual limitation, whereas no difference in the law of taklîf. In line with this case it is the task of Islamic education to maximize their potency and humanity, phisical potency, skill, inteligency, morals, and so on, so that they can run their lively functions, as the the servant of Allah and his caliph. With regard to those explanation, it is important to develope models on the Islamic education children with intelectual disable, so that they will have knowledge, understanding, and experience on Islamic learning, though not as other student. The instruction on the Islamic religion on this type of students formally need to be developed by regarding their character and ability. The Instructional goals must be macthed their intelegency level, the method should be focused on the individual modeling approach with regard on psychology and religion. There must special ability belong to the teacher who teach at the Intelectual dissable school who came from the Islamic Education Department such as good communication skill.